Experimental study of alternative fuel performance operating in single cylinder diesel engine - Khalifaturrahim, Ab Rahman (2013)
This report deals with the performance of waste plastic fuel acting on single cylinder YANMAR diesel engine. The objectives of this project are to analyze the performance of single cylinder YANMAR diesel engine in context of torque and power produced by using waste plastic fuel and compared it with the result obtain by using standard diesel fuel. Second objective is to analyze the consumption of waste plastic fuel compared to the result obtains by using standard diesel fuel available in market nowadays. The project used diesel engine with no load which means there is no force exerted on it. Details studies and research has been done to get knowledge on apparatus and set up for the project.